Building institutions in post-conflict African economies - Janine Aron (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2002)
Institutions are altered by conflict, depending on the scale, duration and type of war. At one extreme, formal political, social and economic institutions may be completely destroyed (e.g. Somalia), while the importance and type of informal institutions may be changed. This survey addresses some of the current issues in the design and implementation of institutional building and reform in developing countries, and highlights the particular difficulties faced by post-conflict countries. However, research on practical policy interventions toward institution-building is still at an early stage. – institutions ; reconstruction ; reform
Keywords: K00; O17; O19; O55; 330; Institutionalismus; Afrika